UPAYA MENINGKATKAN LOYALITAS PELANGGAN JASA MARGA TOUR BANDUNG MELALUI SERVICE ENCOUNTER QUALITY - Fathina, Dina Nur; Malihah, Elly; Setyorini, Heri Puspito Diyah (Universitas Pendidikan Indonesia, 2014)
Tourism service business more and more experience progress and certainly influences to increase working field like tour travel bureau which offer service to travel arrangement. One company in tour travel bureau that develops is Marga Tour Bandung. It focuses to service products into tour package, airlines ticket, and other service. Each service products have the customer. In order to customer loyalty improve continuously, Marga Tour Bandung focuses to how recover employee performance with provide the best service quality when service delivery taking place, on communicating occur between employee and service customer that called service encounter quality. Good service encounter quality will influence customer perception of company service quality, and make the customer continuously to repurchase as the basic to create customer loyalty. Encouraged with premise proposed by Amy Wong (2004:1) that the contact employee in service quality makes an influences customers’ behavioral responses in the form of customer loyalty. Sampling in this research is 80 service customer using stratified random sampling technique. While used data analysis technique is simple linear regression analysis technique with SPSS 17.0 for windows program. The study result shows that service encounter quality has significant influence to customer loyalty. Huge of X variable influence to Y variable is 27%. As suggestion for the company is optimize the elements in service encounter quality, recover the system, as well as provide training to employee so that competence in his field and resulting qualified service.